Legal Protection for Investors in Initial Public Offerings (IPOs): Between Das Sein and Das Sollen - Syazali, Emir Adzan (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2025)
This study examines investor protection in Initial Public Offerings (IPOs) on the Indonesian Capital Market as a mechanism for raising capital that is fraught with information asymmetry and the risk of prospectus misinformation for retail investors. The method used is normative legal research with a legislative and conceptual approach to the Capital Market Law, POJK, IDX provisions, and literature on the principles of full disclosure, due diligence, and law enforcement by the OJK. Normatively, protection is realized through the obligation to provide accurate and non-misleading prospectuses, professional responsibility, OJK supervision, and the right to sue and mechanisms for recovery of losses as preventive and repressive instruments. However, major problems were found in the form of weak consistency in law enforcement, regulatory fragmentation, the heavy burden of proof for investors, the limited effectiveness of class actions, and the lack of clarity in determining the responsible subjects, so that legal certainty and investor confidence are not yet optimal compared to more mature jurisdictions. This study recommends strengthening the design of sanctions, harmonizing regulations, facilitating evidence